Fakhr al-Din al-Razi's Usage of The Poetic and Grammatical Citation to Guide The Qur'anic Recitations (Qira’at) in His Interpretation of (Mafatih al-Ghayb) - Dahmah, Khaled Ali Ali; Sulaiman, Suzana; Alawadi, Elsayed Mohamed Salem; Hidayat, Ahmad Fadhel Syakir (Borneo Journal of Language and Education, 2023)
There is no doubt that reliance on the poetic grammatical citation in directing the Quranic recitations is of great importance, as the interpreter is indispensable in some places from citing a verse of poetry in directing a specific recitation from the recitations (Qira’at). In addition, the grammatical poetic evidence, including what is consecutive and frequent attributed, while others through an unknown lineage. As well as different Quranic recitations according to the languages and dialects of the Arabs (including mutawatir and so on), which makes those interested in linguistics and recitations, seek to know that how to deal with (Al-Fakhr Al-Razi in his interpretation “Mafatih Al-Ghayb”) this poetic grammatical elements, and how did he use it to explain the aspects of the recitations in it. Herein lies the research problem. The importance of the research is that the poetic grammatical citation came to control the difference of the recitations and direct their meaning in order to give preference to the strongest meaning and the most correct way. This research also took the descriptive approach based on the analysis of the poetic citation's passage, the placement of the reason of his citing, the opinion of Al-Fakhr Al-Razi about it, and the comparison between the poetic citation and the recitation, because of the difference in acceptance and rejection. This research came in Ten topics and a conclusion that includes the findings of the researcher, the most important of which are: that Fakhr al-Din al-Razi used in his interpretation of (Mafatih al-Ghayb) poetic and grammatical citation to guide the Quranic recitations. And that the citation he cited for directing the recitation was from the well-known eras of Argumentation, and Fakhr al-Din al-Razi was subject to the grammatical rules of the Qur’anic recitations and marveled at the approach of grammarians who preferred to prove a language with an unknown verse and did not recommend proving it with a continuous seventh recitations.